Authorized heritage : place, memory, and historic sites in prairie Canada - Coutts, Robert, 1953- (University of Manitoba Press, 2021)
"Authorized Heritage analyses the history of commemoration at heritage sites across western Canada. Using extensive research in Parks Canada records, it argues that heritage narratives are almost always based on national and conventional messages that commonly reflect colonialist visions of the past. Throughout western Canada there are vivid examples of original and official views of what constitutes a national narrative. Yet many of the places that commemorate Indigenous, fur trade, and settler colonial histories are contested spaces, places such as Batoche, Seven Oaks, and Upper Fort Garry being the most obvious. At these heritage sites, Indigenous perceptions of the past confront the conventions of settler colonial history and denote the fluid cultural perspectives that must define the shifting ground of heritage space. Robert Coutts brings his many years of experience as a Parks Canada historian to this detailed examination of heritage sites across the prairies. He shows how the process of commemoration reflects social and cultural perspectives that privilege a confident and progressive national narrative. He also examines how class, gender, and sexuality often remain apart from the heritage discourse. Most notably, Authorized Heritage examines how governments became the mediators of what is heritage and, just as significantly, what is not."--